2020
DOI: 10.1186/s12906-019-2780-5
|View full text |Cite
|
Sign up to set email alerts
|

Cordyceps militaris induces apoptosis in ovarian cancer cells through TNF-α/TNFR1-mediated inhibition of NF-κB phosphorylation

Abstract: Background: Cordyceps militaris (L.) Fr. (C. militaris) exhibits pharmacological activities, including antitumor properties, through the regulation of the nuclear factor kappa B (NF-κB) signaling. Tumor Necrosis Factor (TNF) and TNF-α modulates cell survival and apoptosis through NF-κB signaling. However, the mechanism underlying its mode of action on the NF-κB pathway is unclear. Methods: Here, we analyzed the effect of C. militaris extract (CME) on the proliferation of ovarian cancer cells by confirming viab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(92 citation statements)
references
References 53 publications
5
85
0
Order By: Relevance
“…The number of mice surviving in each group and the mortality rate was recorded daily as previously described [ 85 , 86 ]. Animals were observed throughout the experiment to record distress symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…The number of mice surviving in each group and the mortality rate was recorded daily as previously described [ 85 , 86 ]. Animals were observed throughout the experiment to record distress symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, CM had little effect on nonprostatic human endometrial epithelial cells. It is reported that Cordyceps militaris extract inhibited the proliferation of breast cancer, ovarian cancer, nonsmall-cell lung cancer, and colorectal cancer cells through androgen-independent signaling pathways [ 22 , 23 , 24 , 25 ]. Given that the CM-induced decrease in prostate hyperplasia was independent of the serum level of testosterone, CM may regulate the proliferation of prostate cells by inhibiting the activation of intracellular signal pathways other than those involved in testosterone signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Cordycepin is an important metabolite in C. militaris , and possesses the potential as a medicine, food and herbicide [79] , [80] , [81] . In T. guangdongense , extremely low levels of cordycepin were detected, and the genes involved in cordycepin biosynthesis were not identified in the genome of T. guangdongense .…”
Section: Discussionmentioning
confidence: 99%